Retail and marketing channels: Economic and marketing perspectives on producer-distributor relationships - PELLEGRINI, Luca (Institutional Knowledge at Singapore Management University, 2013)
This book contains a selection of the papers presented at the Fourth International Conference on Distribution, held at Bocconi University, Milan, 3 and 4 July 1987.